Methadone maintenance therapy and viral suppression among HIV-infected opioid users: The impacts of crack and injection cocaine use. (1st November 2016) - Socías, M. Eugenia; Wood, Evan; Small, Will; Dong, Huiru; Shoveller, Jean; Kerr, Thomas; Montaner, Julio; Milloy, M-J
Highlights: The effect of methadone maintenance therapy (MMT) on viral suppression varied according to distinct patterns of cocaine use. MMT was associated with increased odds of viral suppression among less than daily cocaine injectors. Daily cocaine injectors did not experience the beneficial impact of MMT on viral suppression. MMT was associated with increased odds of viral suppression regardless of crack cocaine use. Abstract: Background: Methadone maintenance therapy (MMT) is associated with improved HIV treatment outcomes among people who use drugs (PWUD). The extent to which these benefits are sustained in the context of ongoing cocaine use is unclear. We assessed differential impacts of MMT on HIV viral load (VL) suppression in relation to discrete patterns of cocaine use. Methods: Data was drawn from ACCESS, a prospective cohort of HIV-positive PWUD in Vancouver, Canada. Generalized linear mixed-effects were used to model the independent effect of MMT on VL suppression across strata of frequency of cocaine injection and crack smoking (≥daily versus <daily), after adjustment for confounders. Results: The analysis included 397 HIV-positive opioid users who completed ≥1 study interview between 2005 and 2014. At baseline, 304 (77%) reported participation in MMT, 37 (9%) ≥daily cocaine injection, and 158 (40%) ≥daily crack smoking. In adjusted analyses, MMT remained independently associated with increased odds of VL suppression in both strata of crack smokers (AOR = 3.11, 95% CI: 1.86–5.21 and AOR = 1.48, 95%CI: 1.04–2.09, for ≥daily and <daily smokers, respectively), and among <daily cocaine injectors (AOR = 1.88, 95%CI 1.38–2.56), but not among ≥daily cocaine injectors (AOR = 1.37, 95%CI 0.53–3.49). Longer retention on MMT was positively associated with VL suppression in all strata of cocaine injection and crack smoke. Conclusions: Exposure to MMT was associated with increased odds of VL suppression among HIV- positive opioid users regardless of crack use. However, this beneficial effect of MMT was lost among frequent cocaine injectors with shorter retention on MMT.